Analisis Yuridis Tentang Kewenangan Diskresi oleh Kepolisian - Muhammad Khavindra Tamam (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
Indonesia is a constitutional state. As a country that adheres to the rule of law doctrine, the role of the police is crucial, both as a law enforcement agency and as protectors of the community. In carrying out their duties as law enforcement officers, the police are granted the authority to exercise discretion, which allows them to make decisions or take actions based on their own judgment, in accordance with the situation at hand, which must be accountable. The legal basis for the discretionary policy used by the police is regulated in Law Number 2 of 2002, the Criminal Code (KUHP), and national criminal law. The research method used is normative juridical, with a legislative approach and other legal rules, sourced from law journals. Based on this journal's writing, it can be understood that the application of discretion needs to be carried out with caution so that such actions can be accountable, thereby ensuring security, utility, justice, and legal certainty. This journal also highlights that the regulation of discretion has undergone significant development, especially through on National Criminal Law. Under this regulation, the boundaries of police discretion are more clearly defined. However, like other legal regulations, discretion must also be continuously monitored and evaluated to ensure it does not conflict with human rights